Development of PBL Integrated Ethnomathematics Learning Tools to Develop Mathematical Problem-Solving Skills in Elementary School - Diana, Risma Firda; Kusuma, Pratama Surya Bagus (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The low mathematical problem-solving ability of elementary school students is a crucial issue in mathematics learning that has not been optimally addressed. Initial studies suggest that existing learning tools lack cultural context and integration of innovative learning models. Previous research has focused on partial or higher grade levels, leaving gaps in the development of comprehensive problem-based tools for early grade students with local contexts. This research aimed to create Problem-Based Learning (PBL) tools that incorporate ethnomathematics, with the goal of improving students’ mathematical problem-solving skills effectively, practically, and authentically, by utilizing the ADDIE development framework. The research instruments used include learning tools, validation sheets, student response questionnaires, and teacher activity observation sheets. The results demonstrated the validity, practicality, and efficacy of the developed products. The mean percentage of validation for learning module, student response questionnaires, and mathematical problem-solving ability tests was 88.5%, 90%, and 85%, respectively, in the valid category. The average practicality score of the learning tools, assessed through student feedback questionnaires and learning implementation observation forms, was found to be 83.85%, which falls within the practical category. Additionally, the results from the mathematical problem-solving assessments indicated that 80% of the students achieved scores exceeding the minimum competency requirements.